Prevalence of cervical dysplastic lesions in cervical smears from Baghdad city: a single centre study - Mohanad Mahdi Al-Hindawi (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the association of demographic and clinical features of patients with clinicopathological markers in cases of abnormal Pap smear. Method: The retrospective study was conducted from July 2020 to June 2021 at Al-Elwiya Maternity Teaching Hospital, Baghdad, Iraq, and comprised data from January 2019 to June 2020 of women who underwent Pap-smear. Data was retrieved for patients’ age, marital status, smoking status, clinical symptoms at presentation, findings of clinical and cytological examinations, as well as follow-up or human papillomavirus testing data where applicable. Data was analysed using SPSS 26. Results: Of the 560 women with mean age 40.42±10.211 years, 26(4.6%) were attending the hospital for routine check-ups/screening, and 12(2.1%) for follow-up screening with previous abnormal Pap-tests, while the rest had been referred for medical consultation. The most common diagnosis was negative for intraepithelial lesion or malignancy 403(72%) Cervical epithelial abnormalities were seen in 136(24.3%) cases, and, of them, 12(8.8%) returned for follow-up. Epithelial abnormalities had a significant association with age, clinical presentation, and clinical examination results (p<0.05), while it had a non-significant relation with marital and smoking statuses (p>0.05). Conclusion: The majority of subjects were referred cases, with routine cervical screening being <5%. Increasing public awareness about the importance of cervical screening and follow-up is essential. Key Words: Papanicolaou, Uterine Cervical, Papillomavirus Viruses, Demography, Smoking